2022
DOI: 10.1038/s41421-022-00455-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel cyclic γ-AApeptide-based long-acting pan-coronavirus fusion inhibitor with potential oral bioavailability by targeting two sites in spike protein

Abstract: The receptor-binding domain (RBD) in S1 subunit and heptad repeat 1 (HR1) domain in S2 subunit of SARS-CoV-2 spike (S) protein are the targets of neutralizing antibodies (nAbs) and pan-coronavirus (CoV) fusion inhibitory peptides, respectively. However, neither nAb- nor peptide-based drugs can be used orally. In this study, we screened a one-bead-two-compound (OBTC) cyclic γ-AApeptide library against SARS-CoV-2 S protein and identified a hit: S-20 with potent membrane fusion inhibitory activity, but moderate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…Most recently, we have identified a cyclic peptidomimetic, S-20-1, through screening of a one-bead-two-compound (OBTC) cyclic γ-AApeptide library and modification of the compound. 43 We found that S-20-1 effectively inhibited infection of SARS-CoV-2 and its variants,…”
Section: Cyclic Peptidomimetic-based Fusion Inhibitors With Potential...mentioning
confidence: 75%
See 1 more Smart Citation
“…Most recently, we have identified a cyclic peptidomimetic, S-20-1, through screening of a one-bead-two-compound (OBTC) cyclic γ-AApeptide library and modification of the compound. 43 We found that S-20-1 effectively inhibited infection of SARS-CoV-2 and its variants,…”
Section: Cyclic Peptidomimetic-based Fusion Inhibitors With Potential...mentioning
confidence: 75%
“…Therefore, S‐20‐1 has potential for further development as an orally applied therapeutic and prophylactic against SARS‐CoV‐2 and other emerging and reemerging HCoVs. 43 …”
Section: Development Of Pan‐cov Fusion Inhibitorsmentioning
confidence: 99%
“…Most recently, however, we have identified a novel cyclic γ-AApeptide, S-20-1, which has potent fusion inhibitory activity against SARS-CoV-2 and its variants, as well as MERS-CoV, SARS-CoV, HCoV-OC43, HCoV-229E, and HCoV-NL63. It also exhibits long half-life (t 1/2 : 24h) and potential oral bioavailability by targeting SARS-CoV-2 HR1 in S2 subunit and RBD in S1 subunit [ 27 ]. At the same time, we have designed and engineered an HR2-targeting recombinant protein, 5-Helix, which consists of 3 HR1 and 2HR2 fragments.…”
Section: Resultsmentioning
confidence: 99%
“…HIV-1 backbone-based Pseudovirus (PsV) bearing wild or mutant SARS-CoV2 S protein was produced, as previously described [ 27 ]. Caco2 cells were used as target cells and were seeded in wells of a 96-well plate 48 h in advance.…”
Section: Methodsmentioning
confidence: 99%
“…6 ). 137 , 138 In human ACE2, Lys-31 and Lys-353 are sensitive to the RBD. 139 Its glycosylation sites Asn-90 and Asn-322 also demonstrated the ability to interfere with S protein binding in a recent study.…”
Section: Covid-19 Therapeutic Targets For Small Moleculesmentioning
confidence: 99%